1980
DOI: 10.1111/j.1365-2222.1980.tb02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term study of flunisolide treatment in perennial rhinitis with special reference to nasal mucosal histology and morphology

Abstract: Summary Ten patients with allergic perennial rhinitis completed a 3‐month course of treatment with flunisolide nasal spray†. Biopsy of the nasal mucosa was carried out before the initiation of treatment and at the end of the treatment period. The flunisolide was administered as a 0.025% solution twice daily at a total daily dose of 200μg. No histological abnormalities which could have been attributed to the effects of the drug were found in the post‐treatment biopsies. Comparison of the pre‐ and post‐treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…However, Druce [4] and Druce and Slavin [5] indicated that this does not occur when topical corticosteroids are administered concurrently with antibiotics. In other studies Sahay et al [19] found that topical corticosteroids did not cause any perivascular hemorrhage or obvious damage to the walls of blood vessels and any evidence of infection after 12 weeks of treatment.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, Druce [4] and Druce and Slavin [5] indicated that this does not occur when topical corticosteroids are administered concurrently with antibiotics. In other studies Sahay et al [19] found that topical corticosteroids did not cause any perivascular hemorrhage or obvious damage to the walls of blood vessels and any evidence of infection after 12 weeks of treatment.…”
Section: Discussionmentioning
confidence: 86%
“…However, Sahay et al [19] showed that prolonged use of topical corticosteroids did not change plasma steroid levels. Budesonide possesses a high topical and very low systemic activity in contrast to other topical corticosteroids [7,8,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether nasal steroid therapy can suffi ciently decrease nasal infl ammation and improve mucociliary transport to the point at which the ostiomeatal complex becomes competent is unknown. Topical corticosteroids offer the theoretical advantage of a localized therapeutic action in nasal tissues without the occurrence of undesirable systemic effects [42]. A theoretical concern exists regarding the potential spread of infection in acute sinusitis.…”
Section: Corticosteroid Treatmentmentioning
confidence: 99%